Assessment of Data Capture Conditions Effect on Reverse Electrodialysis Process Using a DC Electronic Load - Jesus Nahum Hernandez-Perez; Marco Antonio Hernández-Nochebuena; Jéssica González-Scott; Rosa de Guadalupe González-Huerta; José Luis Reyes-Rodríguez; Alfredo Ortiz (Energies, 2023)
Reverse electrodialysis (RED), an emerging membrane-based technology, harnesses salinity gradient energy for sustainable power generation. Accurate characterization of electrical parameters in RED stacks is crucial to monitoring its performance and exploring possible applications. In this study, a DC electronic load module (DCELM) is implemented in a constant current condition (CC mode) for characterization of lab scale RED process, using a RED prototype in-house designed and manufactured (RU1), at different data capture setups (DCS), on which the total number of steps for data capture (NS) and the number of measurements per step (ρ) are the parameters that were modified to study their effect on obtained electrical parameters in RED. NS of 10, 50, and 100 and ρ of 10 and 20 were used with this purpose. The accuracy of resulting current and voltage steps can be enhanced by increasing NS and ρ values, and according to obtained results, the higher accuracy of resulting output current and voltage steps, with low uncertainty of the average output steps (AOS) inside the operational region of power curve, was obtained using a DCS of NS = 100 and ρ = 20. The developed DCELM is a low-cost alternative to commercial electronic load devices, and the proposed methodology in this study represents an adaptative and optimizable CC mode characterization of RED process. The results obtained in this study suggest that data capture conditions have a direct influence of RED performance, and the accuracy of electrical parameters can be improved by optimizing the DCS parameters, according to the required specifications and the scale of RED prototypes.